2009
DOI: 10.1116/1.3093891
|View full text |Cite
|
Sign up to set email alerts
|

Emission and focusing characteristics of volcano-structured double-gated field emitter arrays

Abstract: Articles you may be interested inFabrication of metallic double-gate field emitter arrays and their electron beam collimation characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…23 To reduce the beam divergence and the transverse electron velocity spread, double-gate FEAs equipped with a beam collimation gate electrode G col in addition to the electron extraction gate electrode G ext have been intensely studied. 5,[7][8][9][24][25][26][27][28][29][30][31] This is due to the fact that the emittance of a FEA can be small only when the individual beamlets are maximally collimated, 1 even though the emittance of individual beamlets is small. 33 In double-gate FEAs, a divergent field emission beam is collimated by applying a negative collimation potential V col to G col .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 To reduce the beam divergence and the transverse electron velocity spread, double-gate FEAs equipped with a beam collimation gate electrode G col in addition to the electron extraction gate electrode G ext have been intensely studied. 5,[7][8][9][24][25][26][27][28][29][30][31] This is due to the fact that the emittance of a FEA can be small only when the individual beamlets are maximally collimated, 1 even though the emittance of individual beamlets is small. 33 In double-gate FEAs, a divergent field emission beam is collimated by applying a negative collimation potential V col to G col .…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge has been lying in minimizing the emission current reduction at the maximum beam brightness. 8,9,[26][27][28][29][30][31][32] We have recently shown that stacked double-gate structures with large G col apertures of approximately 3 times the diameter of the G ext apertures improved the emission current characteristics. 9 To fabricate these double-gate FEAs, we have developed a method using focused ion beam (FIB) milling.…”
Section: Introductionmentioning
confidence: 99%
“…These so-called double-gate FEAs have been proposed as high current and high brightness cathodes 15,16 and have been actively studied. [17][18][19][20][21][22][23][24][25][26] One of the critical obstacles for the realization of high performance double-gate FEAs is the reduction of the emission current during the beam collimation. Recent developments show that this can be circumvented by devising the gate aperture shapes as demonstrated with volcano-shaped FEAs 23 and stacked double-gate device with large G col apertures.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] One of the critical obstacles for the realization of high performance double-gate FEAs is the reduction of the emission current during the beam collimation. Recent developments show that this can be circumvented by devising the gate aperture shapes as demonstrated with volcano-shaped FEAs 23 and stacked double-gate device with large G col apertures. [24][25][26] For the practical application of FEAs it is important to prepare an array with uniform nanotip apex distribution.…”
mentioning
confidence: 99%
“…By applying a negative bias to G col , the fieldemission electron beam can be collimated. [11][12][13][14][15][16][17][18][19] The reported structures differ in terms of location of G col with respect to G ext , as well as in the number of emitters per single G col aperture. Among these, stacked double-gate devices providing a G col aperture for individual emitters exhibit the smallest electron beam emission angle.…”
mentioning
confidence: 99%